Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1007/978-981-10-6955-0_18
|View full text |Cite
|
Sign up to set email alerts
|

The Multiple Roles of Ubiquitylation in Regulating Challenged DNA Replication

Abstract: DNA replication is essential for the propagation of life and the development of complex organisms. However, replication is a risky process as it can lead to mutations and chromosomal alterations. Conditions challenging DNA synthesis by replicative polymerases or DNA helix unwinding, generally termed as replication stress, can halt replication fork progression. Stalled replication forks are unstable, and mechanisms exist to protect their integrity, which promote an efficient restart of DNA synthesis and counter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 128 publications
(128 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, entire loss of CDH1 increased DNA damage accumulation, driving progression of murine and human B-cell acute leukemia [ 138 ]. It was also revealed that many cancer cell lines lack the ability to activate APC Cdh1 when under replication stress [ 139 , 140 ], and that CDH1-depleted cells undergo senescence in G2, suggesting that APC Cdh1 may normally act as a barrier to genome instability [ 123 ]. Support for this idea comes from studies using SIRT2, an antitumor and lifespan-extending protein, which activates the APC by deacetylating CDC20 and CDH1; SIRT2-deficient mice exhibited higher levels of cancer and elevated levels of APC substrates [ 83 ].…”
Section: Targeting Apc Activation For Anticancer Therapymentioning
confidence: 99%
“…Furthermore, entire loss of CDH1 increased DNA damage accumulation, driving progression of murine and human B-cell acute leukemia [ 138 ]. It was also revealed that many cancer cell lines lack the ability to activate APC Cdh1 when under replication stress [ 139 , 140 ], and that CDH1-depleted cells undergo senescence in G2, suggesting that APC Cdh1 may normally act as a barrier to genome instability [ 123 ]. Support for this idea comes from studies using SIRT2, an antitumor and lifespan-extending protein, which activates the APC by deacetylating CDC20 and CDH1; SIRT2-deficient mice exhibited higher levels of cancer and elevated levels of APC substrates [ 83 ].…”
Section: Targeting Apc Activation For Anticancer Therapymentioning
confidence: 99%
“…Some TLS polymerases, such as Pol eta and Pol kappa, play a role in replicating CFSs independent of PCNA (Proliferating Cell Nuclear Antigen) ubiquitylation in both cancerous and normal mammalian cell lines [153][154][155]. However, the ability of evolutionary conserved key TLS enzymes to synthesize DNA in eukaryotes is enhanced by PCNA mono-ubiquitylation [156][157][158][159][160], as reviewed in [161]. The role of ubiquitin and SUMO modifications in DNA replication has been reviewed [162].…”
Section: Dna Synthesis Of Under-replicated Dna Tracks Prior To Mitosismentioning
confidence: 99%